2022
DOI: 10.1158/1541-7786.mcr-21-0681
|View full text |Cite
|
Sign up to set email alerts
|

PDZ Proteins SCRIB and DLG1 Regulate Myeloma Cell Surface CD86 Expression, Growth, and Survival

Abstract: Despite advances in the treatment of multiple myeloma (MM) in the past decades, the disease remains incurable, and understanding signals and molecules that can control myeloma growth and survival are important for the development of novel therapeutic strategies. One such molecule, CD86, regulates MM cell survival via its interaction with CD28 and signaling through its cytoplasmic tail. Although the CD86 cytoplasmic tail has been shown to be involved in drug resistance and can induce molecular changes in MM cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…In the study of Gavile et al [73], it was revealed that CD86 is necessary for myeloma cell survival and drug resistance. Moreover, the cytoplasmic region of CD86 is important for triggering molecular changes, such as the upregulation of Interferon regulatory factor 4 and Integrin beta-1 in myeloma cells [74]. In our study, with the blockade of CD28, the entry of MYXV into myeloma cells was decreased in two of the four patients and increased in one.…”
Section: Discussionsupporting
confidence: 43%
“…In the study of Gavile et al [73], it was revealed that CD86 is necessary for myeloma cell survival and drug resistance. Moreover, the cytoplasmic region of CD86 is important for triggering molecular changes, such as the upregulation of Interferon regulatory factor 4 and Integrin beta-1 in myeloma cells [74]. In our study, with the blockade of CD28, the entry of MYXV into myeloma cells was decreased in two of the four patients and increased in one.…”
Section: Discussionsupporting
confidence: 43%
“…This could occasionally be due to background noise, overlapping of cells, or aggregation of the PE fluorescent dye. Another possible explanation is the incomplete transport or trafficking of newly synthesized CD86 proteins from the Golgi apparatus to the cell membrane [ 46 ]. Nonetheless, these images suggested that CD86 was expressed by the dendritic cells or that the cells were activated by the treatment of IFN-γ and poly I:C simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, it is imperative to acknowledge that the immune response predictions inferred from TIDE were not substantially elevated, intimating a potential resistance of MM to anti-PD1 and anti-CTLA4 therapies. Further research is necessary to elucidate the intricate relationship profoundly and investigate the effectiveness of alternative immunotherapeutic strategies, such as targeting CD47 and CD86 [ [41] , [42] , [43] ]. To conclude, the development of the p53-TIC classifier enhances prognostic stratification in MM patients and facilitates personalized treatment plans, optimizing efficacy and minimizing side effects.…”
Section: Discussionmentioning
confidence: 99%